PIL ANTI HAID UNTUK IBADAH PERSPEKTIF HUKUM ISLAM - Aminullah, Amiruddin (Universitas Islam Negeri Alauddin Makassar, 2023)
Menstruation is a biological process that signifies sexual maturity in women and is associated with Shariah rules in worship. A woman who has experienced menstruation is considered to have reached the stage of adulthood or